Diseño e implementación de un tren de potencia eléctrico en un vehículo de carga liviana para la mejora de eficiencia energética del sistema de tracción - Acosta Gonzales , Jeshua Emanuel (2023)
This research project sought to determine the steps to replace the internal combustion system of a 1977 Datsun pickup truck with an electric propulsion system. The electric conversion process was carried out with the objective of totally eliminating the gases generated by the combustion of the engine when it is in operation. The experimental method was applied, where the fundamental calculations were previously made to determine the power and energy capacity of the main components. It is essential to consider the conditions of urban speed limit, own weight of the vehicle with two occupants, useful load weight and degrees of inclination of a maximum slope. Finally, the route tests were carried out in the city of Otavalo, Selva Alegre parish, with a total distance traveled of 20.98 km, the highest peak power of the three routes was 4.87 kW and the maximum speed at which the vehicle traveled was 59 km/h. Also, through the application of surveys, it was possible to determine the level of acceptance and interest in the project on the part of the people surveyed. Keywords: Electric mobility, electric propulsion, electric vehicle, electromotive power